ASEAN WOMENPRENEURS CONNECT: AI-POWERED MICROBUSINESS COLLABORATION NETWORK - Mutoharoh Mutoharoh; Furtasan Ali Yusuf; Syadely Hanafi; Siti Arofa; Eka Noviani Lestari; Nurasyiah Nurasyiah; Samsul Bahri; Khaerul Ikhwan; Phillip G. Queroda (International Journal of Engagement and Empowerment (IJE2), 2026)
Women's economic empowerment through micro, small, and medium enterprises (MSMEs) constitutes a cornerstone of inclusive growth in the ASEAN region, yet persistent structural barriers such as limited digital literacy, technology access, and cross-border networks hinder women entrepreneurs' participation in the digital economy. While prior initiatives emphasize isolated AI applications or networking, a notable research gap exists in structured models integrating artificial intelligence (AI) with collaborative frameworks to foster sustainable microbusiness ecosystems. This community service study addressed this gap by implementing the ASEAN Womenpreneurs Connect: AI-Powered Microbusiness Collaboration Network at Big Bee Farm, aiming to enhance women micro-entrepreneurs' capacities via technology-driven empowerment and regional collaboration. Employing a Participatory Action Research (PAR) design, the program purposively sampled ASEAN women micro-entrepreneurs facing digital constraints and unfolded through four phases: needs assessment, AI training (e.g., chatbots, content generators), cross-border workshops, and digital network simulations. Data from pre/post-tests, observations, and semi-structured interviews underwent descriptive statistical and thematic analyses. Findings revealed significant gains in digital literacy and AI proficiency for marketing and decision-making, alongside nascent cross-border business networks that spurred product innovation and market expansion; barriers included infrastructure limitations and psychosocial factors. These results imply that integrated AI-collaboration models advance digital entrepreneurship theory and offer practical, replicable tools for women's economic empowerment, informing policy for scalable ASEAN ecosystems.